PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR IPS DI SEKOLAH DASAR - Agus Wandra, Agus Agus; Drs. Muhammadi,M.Si, Drs. Muhammadi,M.Si (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to effect of Contextual Teaching and Learning (CTL) model on student learning outcomes in Social Science Class IV at SDN 15 Ampang Gadang Kabupaten Agam, in the even semester of the academic year 2017/2018. This research is a quantitative research with experimental type and quasy experimental research design. Population of this study amounted to 146 people, sampling data is taken by purposive sampling, with a sample of 37 people. Based on the research that has been done, the average posttest of experiment class 93,3 and control class 88,3 with difference 4,98 number, next research obtained t count> t table, 2.68 > 2.03 with α = 0.05 is means Ho is rejected and Ha accepted, it meaning there is influence the use of Contextual Teaching and Learning (CTL) model of student learning outcomes in Social Science Class IV SD N 15 Ampang Gadang Kabupaten Agam.